2020
DOI: 10.1002/hlca.202000121
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Structural Defects and Impurities on the Excited State Dynamics of 2D BA2PbI4 Perovskite

Abstract: In this work, we show that the quality of the precursor and the thin film preparation strongly affect the optoelectronic properties of the 2D perovskite BA2PbI4. 2D perovskites with alkylammonium organic cations such as butylammonium (BA) are relatively soft structures that exhibit large dynamic disorder and phase variations. Here we show, by a variety of spectroscopy techniques (steady state absorption, photoluminescence and ultrafast transient absorption), that at temperatures below the phase transition (253… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 36 publications
0
26
0
Order By: Relevance
“…The PL property differences between the (BA) 2 SnI 4 film in this study and in literatures , are associated with the quality of the perovskites prepared under different conditions. The corresponding false-color temperature-dependent PL mapping of the (BA) 2 SnI 4 film is shown in Figure c, which reveals a sudden emission peak shift from P1 to P2 at about 225 K. This change in the luminescence properties is a result of the orthorhombic-to-orthorhombic structural phase transition, resembling the phase transition behavior in (BA) 2 SnI 4 , and (BA) 2 PbI 4 , , which primarily stems from a reorientation of the BA + cations in between the inorganic layers ,, or the movement of the essentially rigid BA + cations relative to the inorganic layers. ,, Moreover, according to previous reports, , besides the P1 peak of the high-temperature phase, the P2 of the low-temperature phase can be traced to free-exciton emission. However, the P3 peak below the phase transition temperature may have a different origin of radiative recombination, which will be discussed at the end of this section.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…The PL property differences between the (BA) 2 SnI 4 film in this study and in literatures , are associated with the quality of the perovskites prepared under different conditions. The corresponding false-color temperature-dependent PL mapping of the (BA) 2 SnI 4 film is shown in Figure c, which reveals a sudden emission peak shift from P1 to P2 at about 225 K. This change in the luminescence properties is a result of the orthorhombic-to-orthorhombic structural phase transition, resembling the phase transition behavior in (BA) 2 SnI 4 , and (BA) 2 PbI 4 , , which primarily stems from a reorientation of the BA + cations in between the inorganic layers ,, or the movement of the essentially rigid BA + cations relative to the inorganic layers. ,, Moreover, according to previous reports, , besides the P1 peak of the high-temperature phase, the P2 of the low-temperature phase can be traced to free-exciton emission. However, the P3 peak below the phase transition temperature may have a different origin of radiative recombination, which will be discussed at the end of this section.…”
Section: Resultsmentioning
confidence: 87%
“…Furthermore, A-site organic cations, which are either simple aliphatic and aromatic monoammonium cations or complex and conjugated monoammonium cations, ,,, can also finely tailor the physical and chemical properties of 2D layered organic–inorganic perovskites, ultimately determining the performance and stability of the relevant perovskite optoelectronic devices. A-site organic cations usually have no direct contribution to the construction of valence and conduction band edges.…”
Section: Introductionmentioning
confidence: 99%
“…The normalized PL spectra of the BA 2 PbI 4 film exhibited the main exciton absorption peak (∼510 nm) and an additional PL feature at ∼560 nm, whereas the PL spectrum of the BA 2 MAPb 2 I 7 film had a main peak at ∼590 nm. The lower-energy PL tail of low-dimensional perovskite material comes from the radiative recombination of trap states and/or strong phonon coupling with the distorted soft crystal structure. A recent report by Chen et al suggested that PL peaks at 540, 580, 620, 680, and 700 nm in PEAI–MAPbI 3 mixed perovskites were assumed to be n = 1, 2, 3, 4, and 5, respectively. The n -value of the RP phase in the PEAI–MAPbI 3 mixed perovskite can be tuned by the reaction temperature .…”
Section: Resultsmentioning
confidence: 99%
“…This is consistent with experimental observations of the differences in structural rigidity between PEA and BA. 26 , 46 When the length of the linker is increased such as in the POB compound, the flexibility of the amide is increased, but the rigidity of the aromatic part of the material is maintained. The latter leads to a strongly enhanced resistance to moisture while leaving the structural rigidity of the inorganic part unaffected.…”
Section: Resultsmentioning
confidence: 99%